Implementasi Kebijakan Pajak Reklame di Kabupaten Pati - Vian Widya Hapsari; Sundarso Sundarso; Aufarul Marom (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
Policy Advertisment Tax is the policy was included in the law number 28 of 2009 about local taxes and retribution, having the objective among others to set local tax and retribution, giving authority greater to the regions in process, and management governing taxes and retribution in the its. In line with the amount of responsibility region in implementing governance and public service. In Pati Regency, advertisement tax policy implementation set forth in regulations of the area number 3 in 2011 about tax areas, where the regulation of this area, is expected to overcome the problems about advertisement tax during this time. These problems includes : taxpayers who did not pay his taxesin a timely manner, of any installation and installation of the advertises wild does not pay attention to the aesthetics of the city. The goal can be achieved through an effective implementation process that can be seen from the policy implementation, precision accuracy, accuracy environmental targets and the precision of the process.The implementation of advertisment tax in achieving the goal of supporting and hindering factors. Based on the teory of Van Meter and Van Horn, factors that Resource policy, communication and implementation activities, the implementing agency characteristics, Sosial, Economic, Politic conditions as well as the disposition of the implementor.Based on the existing obstacles in the implementation of advertisment tax in the District of Pati, the authors provide recommendation in the form of : (1) Providing socializing purposes and tax policy legal basis to tax payers clearly understand the rules regarding advertisement tax policy. (2) In granting Assertiveness penalities that will be imposed on the taxpayers in case of violations, violations of either delay tax payers paid his taxes and offense ads implementation without permission. (3) Conducting and supervision regularly, in other to minimize the existence of the problem of illegal tax that is not registered in field. (4) The increase of the number of staff good who handles policy advertisement tax in dept or on a field and adding supporting the form of computer.